2020
DOI: 10.1016/j.addbeh.2019.106117
|View full text |Cite
|
Sign up to set email alerts
|

Free-viewing multi-stimulus eye tracking task to index attention bias for alcohol versus soda cues: Satisfactory reliability and criterion validity

Abstract: Free-viewing multi-stimulus eye tracking task to index attention bias for alcohol versus soda cues: Satisfactory reliability and criterion validity. Addictive Behaviors, 100, [106117].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 36 publications
(48 reference statements)
3
25
0
1
Order By: Relevance
“…However, the high error rate of the OOOT may have prevented it from having sufficient sensitivity to adequately capture the effects of the BITT on AB [ 51 ]. Future studies may benefit from using an improved version of the OOOT (for recommendations, see [ 52 ]) or an alternative AB task with better psychometric properties (for example based on eye-tracking procedures such as described in [ 53 ]) to index the impact of ABM on individuals’ AB.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high error rate of the OOOT may have prevented it from having sufficient sensitivity to adequately capture the effects of the BITT on AB [ 51 ]. Future studies may benefit from using an improved version of the OOOT (for recommendations, see [ 52 ]) or an alternative AB task with better psychometric properties (for example based on eye-tracking procedures such as described in [ 53 ]) to index the impact of ABM on individuals’ AB.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study examined the reliability indices of a recently developed free-viewing eye-tracking paradigm within the eating disorder context. The same free-viewing paradigm has been employed within the context of social anxiety (Lazarov et al, 2016), depression (Lazarov et al, 2018), and alcohol consumption (Soleymani et al, 2020) and has shown good to excellent internal consistency for the dwell-time based indices.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we examined the reliability of a modified version of the free-viewing task originally designed by Lazarov et al (2016) as a measure of attentional bias to food pictures. Consistent with previous studies (Lazarov et al, 2016(Lazarov et al, , 2018Soleymani et al, 2020), we computed eye-tracking measures of both early (first fixation location and latency) and later attention (total dwell time), and examined their relationships with measures of several relevant constructs i.e. self-report measures of hunger, dietary restraint, general and eating-related rumination, eating disorder symptoms, and subjective attitudes towards food images.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations